Drying kinetics of cinnamon (Cinnamomum zeylanicum J. Presl) leaves: effects on individual volatile compounds and external color - Celia, Juliana Aparecida (2018)
The post-harvest stage of crops aims to minimize losses occuring during storage and commercialization. Drying process are some of the most used methods to minimize those losses. This work aimed at studying the drying kinetics of cinnamon (Cinnamomum zeylanicum), subject to two different drying conditions, one of which in an experimental fixed-bed dryer relying on an ambient air and speed of 0.5 m s-1, and the other with a forced air circulation oven at different temperatures (313.5, 323.15, 333.15 and 343.15 degrees K). The time required to reach the moisture equilibrium contents was 1.42, 3.0, 6.41, 14.0 and 21 h for drying temperatures of 343.15, 333.15, 323.15, 313.5 and 307.95 oK, respectively. The Arrhenius equation described the diffusivity's dependence on temperature, defining the activation energy of 64.77 kJ mol-1. The essential oils of the samples were analyzed through gas chromatography, which identified 23 individual compounds being eugenol the most abundant.